2018
DOI: 10.1016/j.jid.2018.03.639
|View full text |Cite
|
Sign up to set email alerts
|

630 Growth differentiation factor 11 (GDF11) modulation in skin rejuvenation

Abstract: We previously showed that topical application of hexoses such as fructose accelerates stratum corneum barrier recovery after barrier disruption. We also showed that various hexoses and polyols interact with phospholipids and decrease the phase transition temperature from the liquid crystal to the crystal phase; i.e., they stabilize the fluid phase of lipids at low temperature. In the present study, we confirmed that topical application of xylitol aqueous solution on human skin after tape stripping accelerated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Stability test results showed this mixture is stable for a week in refrigerated condition (data not shown). Lemestr et al showed that GDF-11 decreased fibroblast senescence [36] . However, it is still unclear if GDF-11 can enhance skin regeneration via human applied.…”
Section: Discussionmentioning
confidence: 99%
“…Stability test results showed this mixture is stable for a week in refrigerated condition (data not shown). Lemestr et al showed that GDF-11 decreased fibroblast senescence [36] . However, it is still unclear if GDF-11 can enhance skin regeneration via human applied.…”
Section: Discussionmentioning
confidence: 99%